Application of chemotherapy combined with immunotherapy in first-line treatment of advanced esophageal cancer: fluorouracil or paclitaxel? – a meta-analysis - Chen, Xiaochen; Yan, Huiping; Zhao, Hongyang; Zhu, Pengfei (Frontiers in Oncology, 2025)
IntroductionImmunotherapy combined with chemotherapy is now the first-line standard for metastatic/recurrent esophageal cancer, with rapid immunotherapy advancements significantly improving patient outcomes. International guidelines recommend platinum-based combinations with either 5-fluorouracil or paclitaxel as first-line treatments. Currently, no head-to-head studies directly compare fluorouracil and paclitaxel regimens in esophageal cancer.MethodsWe systematically searched online literature for clinical trials investigating first-line immunotherapy-chemotherapy combinations for esophageal cancer. Data were analyzed using Review Manager (RevMan) 5.3 software, with pooled results expressed as odds ratios (ORs) and 95% confidence intervals (CIs).ResultsBoth paclitaxel- and fluorouracil-based immunotherapy combinations demonstrated clinical benefits in overall survival, progression-free survival, and objective response rates. Notably, paclitaxel-based immunotherapy significantly increased ORR compared to fluorouracil-based regimens (OR 2.61 vs 1.58).DiscussionOur findings suggest that paclitaxel-immunotherapy combinations may offer enhanced disease control compared to fluorouracil-based approaches, warranting further studies to identify optimal patient populations and refine treatment strategies.